THE RELATIONSHIP BETWEEN LONG WORK DURATION PER DAY AND THE RISK OF NON SPECIFIC LOW BACK PAIN IN ONLINE MOTORCYLE TAXI DRIVERS - Putri, Ardilia Gilang; Mulyadi, Soffil Yudha (International Journal Multidisciplinary (IJMI), 2025)
Objective: The purpose of this study was to determine whether there is a relationship between the duration of work per day with the risk of non-specific low back pain in online motorcycle taxi drivers. Method: The type of research is quantitative with a cross-sectional approach which will be carried out in January 2024. The respondents in the study were online motorcycle taxi riders in the Sidoarjo area with a sample of 97 respondents using Kolmogorov-Smirnov. Results: Based on the results of a survey that has been conducted on the working hours of online motorcycle taxi drivers, the majority of respondents in this study work 7 to 9 hours per day with a maximum number of 35 people, and working hours ≤ 10 hours per day, p-value 0.001 < (0.00). Shows there is a relationship between the duration of work and the risk of non-specific Low Back Pain. Novelty: This study highlights the occupational health risks specific to online motorcycle taxi drivers in the Sidoarjo area, which has not been extensively explored in prior research, particularly concerning non-specific low back pain associated with daily working duration.